Study on Contraceptive Oral Pills on Reproductive Physiology of Female Albino Rat: Exploring the efficacy of medicinal plants as contraceptive agents in female albino rats (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Point and Objective The point of this survey was to give a nitty gritty idea to the analysts on antifertility action of a few plants restraining male and female ripeness and might be formed into contraceptives. Regardless of numerous therapeutic plants have been professed to forestall ripeness, just couple of plants were so far been researched for their antifertility action. Materials and Methods A broad bibliographic examination was completed by breaking down different traditional course books, logical diaries, counseling overall acknowledged data sets for giving reasonable data on antifertility therapeutic plants. Plant species generally utilized as contraceptives, abortifacients, emmenagogues, spermatogenics were considered as antifertility specialists. Results Overall 233 plant species having a place with different families, generally utilized as antifertility specialists in the two guys and females has been incorporated in this audit. The different plant parts utilized in richness guideline incorporates leaves, natural products, roots, bark, stem and so forth All in all, unmistakably therapeutic plants assume a significant part as antifertility specialists. Notwithstanding of different financially accessible oral contraceptives on the lookout, home grown antifertility specialists shows promising yield by limiting the quantity of unfavorable medication properties. Ebb and flow research towards conventional medication is developing quickly due to its security and less expense utilization.